Network pharmacology and transcriptomics reveal the mechanisms of FFBZL in the treatment of oral squamous cell carcinoma - Zhao, Shiyang; Xiao, Shudong; Wang, Wanting; Dong, Xinyue; Liu, Xichen; Wang, Qingsen; Jiang, Yourong; Wu, Wen (Frontiers in Pharmacology, 2024)
Background: FFBZL has been reported to be effective in the treatment of oral squamous cell carcinoma (OSCC). However, the molecular mechanism involved remains unclear. Materials and methods: The TCMSP, ETCM, and SymMap databases were utilized to collect information on the active constituents and targets of FFBZL, while the PharmMapper database was used to predict targets. Differential gene expression analysis was conducted to identify targets associated with OSCC, and these targets were subsequently aligned with targets of the effective components of FFBZL to identify common targets. Next, 71 targets were rescreened using the PPI network, and GO and KEGG enrichment analyses were performed; the PI3K-Akt signaling pathway was the top-ranking pathway related to cell apoptosis. The targets were subsequently mapped to the PI3K-Akt signaling pathway using the KEGG database, and the GSEA algorithm was used to assess the overall expression trend of the genes in this pathway. The DEGREE and MCC algorithms were used to select the corresponding targets within the PPI network. Subsequently, the UALCAN database was utilized to analyze the expression levels and survival associations of the key genes related to cell apoptosis, and the transcriptome data from the GEO database were used to assess the correlations among the 6 key genes. Finally, molecular docking studies were conducted. Results: GO and KEGG enrichment analyses revealed that most of the top-ranked functions and pathways were associated with apoptosis, with the PI3K-Akt signaling pathway playing a critical role. Transcriptome analysis of data from the TCGA and GEO databases indicated that the genes enriched in the PI3K-Akt signaling pathway were strongly upregulated, and the GSEA algorithm indicated an overall upregulation trend for the PI3K-Akt signaling pathway. The mRNA and protein expression levels of most these targets in head and neck squamous cell carcinoma were higher than those in normal tissues. Survival analysis revealed that low expression of SPP1 and FN1 was associated with increased patient survival time. Additionally, the molecular docking results indicated strong binding potential between the six identified key components and the six key targets.